The Political Economy of Slavery in the Dutch Empire - Brandon, Pepijn (Comparativ, 2021)
The Dutch Republic and its successor state the Kingdom of the Netherlands were deeply involved in slavery and the slave trade in the Atlantic and Indian Ocean world. Its most intense involvement roughly coincides with the period in which this small country played an outsized role in the development of the ligaments of global capitalism – coupling domestic capital accumulation with a prime role in world trade, international finance, commercial warfare and the spread of new forms of calculative reasoning. This combination makes the Dutch case an important one for investigating the ways in which capitalism and slavery co-constituted each other in a crucial phase of transformation of the global economy. However, narrowing down the question of the relationship between capitalism and slavery to the much more limited question whether the profits from slavery fueled a domestic industrial revolution, has led many authors in the past to simply out of hand dismiss the relevance of this problematic for Dutch history. This article seeks to show why and how for the Dutch, over the course of several centuries and in a large number of constellations across and beyond its territorial reach, capitalist development and different forms of commercial slavery became joined at the hip. Since in this relationship neither capitalism nor slavery were stable entities, the ways in which they were mutually integrated (constituting the political economy of the Dutch participation in slavery) also stemmed from different motives and aims across geographies, varied in intensity, and underwent substantial change over time.